Early modern European diplomacy a handbook - Goetze, Dorothée 1981-; Oetzel, Lena; Buchbauer, Georg (De Gruyter Oldenbourg, 2024)
New Diplomatic History has turned into one of the most dynamic and innovative areas of research - especially with regard to early modern history. It has shown that diplomacy was not as homogenous as previously thought. On the contrary, it was shaped by a multitude of actors, practices and places. The handbook aims to characterise these different manifestations of diplomacy and to contextualise them within ongoing scientific debates. It brings together scholars from different disciplines and historiographical traditions.The handbook deliberately focuses on European diplomacy - although non-European areas are taken into account for future research - in order to limit the framework and ensure precise definitions of diplomacy and its manifestations. This must be the prerequisite for potential future global historical perspectives including both the non-European and the European world